Aiyyaa (Hindi Film) - Trivedi, Amit 1979- (Super Cassettes, 2012)
A middle-class Marathi mulgi falls in love and romances a Tamil boy in her quirky fantasies, while her parents are looking for the perfect matrimonial match
DVD; anamorphic widescreen; Dolby digital 5.1
Rani Mukherji, Prithviraj, Subodh Bhave
Music, Amit Trivedi ; produced by Viacom 18 Motion pictures, Anurag Kashyap, Guneet Monga